Prevention and treatment of parastomal hernia: a position statement on behalf of the Association of Coloproctology of Great Britain and Ireland. (19th July 2018) - ,
Abstract: Aim: The Association of Coloproctology of Great Britain and Ireland (ACPGBI) Delphi process identified prevention and treatment of parastomal hernia (PSH) as the second highest priority non‐cancer related colorectal pathology. This position statement aims to summarize the current evidence base. Methods: Four broad themes were identified (prevention, diagnosis/classification, management and operative repair). Guidelines are based on evidence from an extensive literature review using organized searches on the PubMed, MEDLINE, Embase and Cochrane databases. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system was adhered to for classifying the quality of evidence and reporting the strength of recommendations. Results: The suture repair of PSH other than for patients in extremis is not recommended. Synthetic non‐absorbable mesh can be used safely in the short term in the construction of colostomies post rectal surgery, but longer‐term follow‐up is needed. Other broad recommendations are made around access to stoma care nurses, prevention classification and management. Conclusion: There is a lack of high quality evidence for many domains in the prevention and treatment of PSH but the results of several studies are awaited. What does this paper add to the literature?: Parastomal hernias are a common and debilitating condition following stoma formation. This position statement from ACPGBI details the current evidence base and ongoing research for the prevention, diagnosis and management of parastomal hernias.